Investigation of relationship between sediment characteristics and heavy metals across seasons in the Lower Focardos River, Nigeria - Onari Asimiea Aminayanaba; Olanrewaju Lawal (Journal of Applied Sciences and Environmental Management, 2017)
The presence and concentration of heavy metals in water bodies may be influenced by human activities. Sediments are the final sink of heavy metals in the water body. This study examined the concentration of heavy metals in the sediments across the outlet of the Forcados. This was intended to examine the relationship between sediment characteristics and heavy metal concentration across the seasons. Samples were taken across two seasons and tested for heavy metals. Correlation analysis was used to test association between sediment characteristics and heavy metal concentration, while Mann-Whitney U test was adopted to test the difference across seasons. Results show that Total Organic Carbon (TOC) and the particle size distribution have a significant relationship (P<0.05) with correlation coefficient -0.272 and 0.335 for sand and silt respectively. TOC was also found to be positively and significantly correlation with all the heavy metal tested, while V, Ni, Cr, Pb, Cu displayed significant correlation with particle size distribution. Across these seasons, significant difference (P<0.05) was recorded for oil/grease (OGRS), Total Petroleum Hydrocarbon (TPH), TOC, Sand, Clay, Cr, Fe, As, Ba and Zn. Association between particle size and OGRS gives an indication that, while oil spill in a sandy environment may seep in deeper, the depth of permeation of oil spill in fine particle sediment could be limited. It was concluded there are marked variations in heavy metals across seasons and there is an association between these concentration and the characteristics of the sediment. This understanding is important for prioritization of remediation.